PENILAIAN EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA INDUSTRI HOTEL DI KAWASAN BTDC NUSA DUA BALI - Wiratama, I Putu Gede Aditya; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi, 2014)
Technology development these days is so fast. This make Accounting Information System also take part in the progress. The evidence is from so many hotels that implement a computerized accounting information system. This research has purpose to know effectiveness of Accounting Information Systems used by hotels in BTDC sector. The amount of sample used is 76 people that specified by non probability sampling method, which is purposive sampling. Data collecting is done by interview and questionnaires. Analysis technique that used is quantitative analysis technique. Based on the analysis result concluded that Accounting Information Systems that is used at hotel in BTDC sector is effective. Based on that analysis result then each hotel must keep and increase quality and its employee performance and give training that related to Accounting Information System.
Keywords: effectiveness of hotel Accounting Information Systems